ASSESSING THE IMPACT OF INTEGRATED SKILL TEACHING ON EFL LEARNERS' MOTIVATION AND ENGAGEMENT - Muhammad Abdul Azis (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2023)
English as a Foreign Language (EFL) learning is a crucial aspect of education for millions of students globally. Traditional language instruction often focused on isolated skill development, but integrated skill teaching approaches have gained popularity in recent years. These approaches aim to create authentic and meaningful language learning experiences by connecting language skills and embedding them in real-life contexts. This study assesses the impact of integrated skill teaching on EFL learners' motivation and engagement. The research was conducted with a diverse group of EFL learners in (describe the setting), utilizing a mixed- methods design. Quantitative surveys and qualitative interviews were employed to gather comprehensive data on learners' motivation and engagement levels. The findings demonstrate that integrated skill teaching fosters a deeper connection to the language, leading to improved fluency, communicative competence, and a sense of relevance in language use. Learners' increased enthusiasm and willingness to actively engage in the learning process underscore the effectiveness of this approach in empowering EFL learners. The research contributes valuable insights for educators, curriculum developers, and policymakers to design more effective language programs that enhance learners' motivation and engagement, ultimately leading to improved language proficiency and overall language learning experiences.